Stability and change in risk-taking propensity across the adult life span. [article]. - Josef, Anika K.
Can risk-taking propensity be thought of as a trait that captures individual differences across domains, measures, and time? Studying stability in risk-taking propensities across the life span can help to answer such questions by uncovering parallel, or divergent, trajectories across domains and measures. We contribute to this effort by using data from respondents aged 18 to 85 in the German Socio-Economic Panel Study (SOEP) and by examining (a) differential stability, (b) mean-level differences, and (c) individual-level changes in self-reported general (N = 44,076) and domain-specific (N = 11,903) risk-taking propensities across adulthood. In addition, we investigate (d) the correspondence between cross-sectional trajectories of self-report and behavioral measures of social (trust game; N = 646) and nonsocial (monetary gamble; N = 433) risk taking. The results suggest that risk-taking propensity can be understood as a trait with moderate stability. Results show reliable mean-level differences across the life span, with risk-taking propensities typically decreasing with age, although significant variation emerges across domains and individuals. Interestingly, the mean-level trajectory for behavioral measures of social and nonsocial risk taking was similar to those obtained from self-reported risk, despite small correlations between task behavior and self-reports. Individual-level analyses suggest a link between changes in risk-taking propensities both across domains and in relation to changes in some of the Big Five personality traits. Overall, these results raise important questions concerning the role of common processes or events that shape the life span development of risk-taking across domains as well as other major personality facets. -- (from the authors)